2011
DOI: 10.1089/jwh.2010.2657
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression in the United States: Nationally Representative Rates and Risks

Abstract: Maternal depression is a major public health problem in the United States, with an estimated 1 in 10 children experiencing a depressed mother in any given year. Professionals who work with mothers and children should be aware of its prevalence and its detrimental effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
218
7
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(237 citation statements)
references
References 64 publications
10
218
7
2
Order By: Relevance
“…This is further increased by selective attrition among socially disadvantaged women. As it is likely that this group has a higher proportion of maternal depression (Ertel et al 2011), our results are plausibly an under-rather than an over-estimate of the relationship between socio-economic predictors and maternal depression trajectories. Replication of our findings in a population including a higher proportion of disadvantaged, high-risk families is warranted.…”
Section: Strengths and Limitationsmentioning
confidence: 71%
“…This is further increased by selective attrition among socially disadvantaged women. As it is likely that this group has a higher proportion of maternal depression (Ertel et al 2011), our results are plausibly an under-rather than an over-estimate of the relationship between socio-economic predictors and maternal depression trajectories. Replication of our findings in a population including a higher proportion of disadvantaged, high-risk families is warranted.…”
Section: Strengths and Limitationsmentioning
confidence: 71%
“…Depression is prevalent in parents with children: data from the National Epidemiologic Survey of Alcohol andRelated Conditions in 2001-2002 shows that 10 % of mothers in the US are affected by depression (Ertel et al 2011); and a recent meta-analysis on paternal depression has reported that 5-10 % of fathers are depressed (Paulson and Bazemore 2010). Sub-clinical levels of depressive symptoms are even more prevalent and also have negative consequences for children (Cummings et al 2005;Farmer et al 2002;Silver et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a nationally representative sample of the civilian population of the United States (N = 8916), part of the National Epidemiologic Survey of Alcohol and Related Conditions, maternal depression was found to be a major public health problem in the United States impacting 10% of new mothers and their families (Ertel, Rich-Edwards, & Koenen, 2011). International studies have demonstrated that salient features of maternal depression can impair the maternal infant relationship (Edhborg, Nasreen, & Kabir, 2011;Moehler, Brunner, Wiebel, Reck, & Resch, 2006) and adversely impact a child's cognitive development, social skills, and behavior (Grace, Evindar, & Stewart, 2003;Tronick & Reck, 2009;Wu, Selig, Roberts, & Steele, 2011).…”
Section: Maternal Depression and Maternal Infant Relationshipmentioning
confidence: 99%